2017
DOI: 10.1159/000458755
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Intravenous Injection Form and Oral Jelly Form of Alendronate Sodium Hydrate for Bone Mineral Disorder after Gastrectomy

Abstract: Background/Aims: Osteoporosis is found to have high prevalence after gastrectomy and therefore, it is important to prevent this condition by means of effective medication, such as alendronate sodium hydrate. Methods: A total number of 48 gastric cancer patients diagnosed with osteoporosis after R0 gastrectomy was registered in this study between December 2013 and August 2014. Twenty-three patients received intravenous (i.v.) alendronate sodium hydrate and 25 patients received the drug in an oral jelly form. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Although the time course changes in the mean values of bone turnover markers (TRACP-5b and P1NP) did not differ significantly between the two treatment groups in this study, both treatment formulations significantly decreased the level of TRACP-5b by approximately 50% and that of P1NP by approximately 60% from baseline to 6 months (both P < 0.0001). Similarly, in the study by Kunisaki et al, 44 both treatments decreased TRACP-5b and P1NP over time. On the basis of these results, we consider that the jelly formulation has an equivalent potential to achieve similar therapeutic effects compared with the tablet formulation.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Although the time course changes in the mean values of bone turnover markers (TRACP-5b and P1NP) did not differ significantly between the two treatment groups in this study, both treatment formulations significantly decreased the level of TRACP-5b by approximately 50% and that of P1NP by approximately 60% from baseline to 6 months (both P < 0.0001). Similarly, in the study by Kunisaki et al, 44 both treatments decreased TRACP-5b and P1NP over time. On the basis of these results, we consider that the jelly formulation has an equivalent potential to achieve similar therapeutic effects compared with the tablet formulation.…”
Section: Discussionsupporting
confidence: 65%
“…Further study is needed to evaluate the differences in effectiveness between the two formulations. Kunisaki et al recently performed a comparative study of sodium alendronate in intravenous injection and oral jelly form in gastric cancer patients . They found that BMD increased in both groups, and there were no significant differences between groups in terms of efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 For osteoporosis after gastrectomy, some studies showed that alendronate might improve osteopenia 20 or might prevent bone mineral disorders and fractures. 5 , 21 , 22 However, these studies used a relatively small sample size, and no clear evidence has been established concerning their effectiveness. Particularly, bisphosphonates have various digestive complications, and the safety and feasibility of bisphosphonates in the special gastrointestinal environment after gastrectomy are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of drug in the structure provides an opportunity for taste masking and avoids the need for drinking water [7]. Several products of chewable gels and dosage forms are commercially available, particularly for the delivery of vitamins [8], mineral supplements [9], nutrition [10], as well as for the treatment of osteoporosis [11,12]. However, formulating chewable oral doses is often associated with challenges regarding drug stability and the capacity for higher doses.…”
Section: Introductionmentioning
confidence: 99%